Pemanfaatan Waktu Belajar Siswa Di Luar Jam Sekolah Melalui Kegiatan Ekstrakulikuler Keagamaan - Eko Nursalim; Hapriliani Hapriliani; Muhammad Awie Mas’ud; Mey Nuri Hafidha Sari; Amrin Batua (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2024)
This research is based on the relatively short study time of students. Therefore, to optimize or utilize spare time, activities are needed that can develop students' personalities in terms of morality, worship, and achievement. One of the informal institutions based on Islamic boarding school that has utilized spare time is the Paqusatta Islamic boarding school, located in the North Sangatta district, Kutai Timur regency. The adapted research method we used is a qualitative field method involving data collection, observation, and interviews. The utilization of students' study time outside of school hours through Islamic boarding school activities has significant objectives in education, especially in shaping character with morality and achievement. Therefore, this research aims to explore ways to utilize students' study time outside of school hours through Islamic boarding school activities to shape students' moral and high-achieving characters. This research uses a qualitative approach to collect data, relationships, cause and effect, and factors influencing the utilization of spare time in students. The aim is to determine the methods used by teachers in utilizing students' spare time, exemplified through religious activities and the implementation of extracurricular programs in Islamic boarding school, aiming to enhance the utilization of spare time in shaping moral and high-achieving characters in students.